2002
DOI: 10.1128/jvi.76.10.5108-5120.2002
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Modulation of Human Immunodeficiency Virus Type 1 Rev Function by cis and trans Regulators of Viral RNA Splicing

Abstract: Expression of the entire complement of human immunodeficiency virus type 1 (HIV-1) viral proteins depends on the competing activities of viral RNA splicing and export into the cytoplasm by Rev. To investigate the possibility that modulation of viral RNA metabolism may alter Rev function, we analyzed the impact of multiple SR proteins on both processes. While overexpression of several of the SR factors altered splicing of HIV-1 env mRNA, they had disparate effects on Rev function that varied with the cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…Moreover, the ESE and ESS within the terminal exon also regulate viral RNA transport. Deletion of the ESE results in loss of Revinduced transport of the unspliced RNA to the cytoplasm (Pongoski et al 2002). The inhibition of Rev-induced RNA transport is ESS dependent because deletion of both the ESE and the ESS restores transport of the RNA.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ESE and ESS within the terminal exon also regulate viral RNA transport. Deletion of the ESE results in loss of Revinduced transport of the unspliced RNA to the cytoplasm (Pongoski et al 2002). The inhibition of Rev-induced RNA transport is ESS dependent because deletion of both the ESE and the ESS restores transport of the RNA.…”
Section: Introductionmentioning
confidence: 99%
“…Retroviruses use many general SREs to regulate splicing of their RNA (for review, see Stoltzfus and Madsen 2006) and also use RNA elements to regulate nuclear export of unspliced RNA (for reviews, see Pollard and Malim 1998;Cullen 2003). How HIV RNAs balance between the two pathways is not completely clear, but some common elements might serve as a functional bridge between the two pathways by participating in the regulation of both splicing and RNA export (e.g., an ESS recognized by hnRNP A1 [Asai et al 2003] and the Rev response elements [Pongoski et al 2002]). …”
Section: Elements That Regulate Intron Retentionmentioning
confidence: 99%
“…The combination of these various sites gives rise to at least 35 different mRNAs (1). Although the relative efficiencies of the HIV-1 donor sites seem to depend mainly upon their complementarity to the U1 snRNA 5Ј-terminal sequence (3,4), efficiencies of HIV-1 acceptor sites depend upon the presence of cis-regulatory elements (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Several studies have shown that HIV-1 acceptor sites are suboptimal as follows.…”
mentioning
confidence: 99%
“…Although variations of the cellular concentrations of some of the SR proteins, namely SC35 and 9G8, have been observed after cell infection by virus HIV-1 (37,38), little is known about the action of SR proteins on the competition between the eight splicing acceptor sites and four splicing donor sites of HIV-1 RNA. The present knowledge in this field can be summarized as follows: (i) deep studies, which were performed both in vitro and in vivo, demonstrated the action of proteins ASF/SF2 and SC35 at acceptor site A7 (17,19,20,39,40); (ii) an in vitro study performed with S100 extract showed that, among the SR proteins SC35, SRp40, SRp55, and SRp70, only protein SC35 is able to activate site A3 in S100 extract (41). For a complete study of the effects of individual SR proteins on the entire set of HIV-1 splicing sites in cellular conditions, we cotransfected HeLa cells with a construct that produces a truncated HIV-1 RNA containing all the splicing sites (13,24), and a plasmid that overexpresses one of the SC35, SRp40, ASF/SF2, and 9G8 SR proteins.…”
mentioning
confidence: 99%